The Phenomenon of Mass Organization Intervention in the Development of the Electric Car Industry in Indonesia - Irfan Sobari (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
The phenomenon of civil society organisations (CSOs) intervening in industry often causes serious problems, both for the industry itself and for the government and society. This study aims to analyse the forms, motives, and impacts of CSO intervention on the development of the electric car industry, including its implications for government policy, investment, and public acceptance. The research method used is a qualitative approach with a systematic literature review of media reports on the electric automotive industry in Indonesia. The results of the study show that CSOs play a role in intervention in the form of extortion or illegal levies, financial, psychological, social relations, mass media, administrative, power, and business. This study concludes that CSO involvement in the electric car industry has a negative impact, and clear regulations are needed so that intervention can support sustainable development in Indonesia's electric automotive sector.